ХАМҚОРЛИК ПЕДАГОГИКАСИ АСОСИДА УМУМИЙ ЎРТА ТАЪЛИМ МАКТАБЛАРИ ЎҚИТУВЧИЛАРИНИНГ КАСБИЙ КОМПЕТЕНТЛИГИНИ РИВОЖЛАНТИРИШДА КРЕАТИВ ТЕХНОЛОГИЯЛАРНИНГ ЎРНИ - Умаралиева, М. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of the creative abilities of the teacher, and how to solve practical problems of their formation. The author of the article describes the types of pedagogical skills, creative aspects of professional competence, and the scientific and professional skills of teachers secondary schools.